A benzophenoxazine-based NIR fluorescent probe for the detection of hydrogen sulfide and imaging in living cells. Issue 20 (14th September 2022) - Yin, Wenzhu; Wang, Hongjing; Ma, Fang; Xu, Zeyu; Lu, Yu; Zhou, Mingxu; Deng, Bihua; Wang, Haiyan; Zhang, Jinqiu
Abstract : Fluorescence probe NRDNP exhibits excellent sensing performance toward H2 S with about 80-fold fluorescence enhancement. The excellent sensitivity and a detection limit of 19 nM make it application for fluorescence imaging of H2 S in living cells. Abstract : Hydrogen sulfide (H2 S) plays a vital role in regulating many important physiological functions. However, H2 S-containing industrial wastewater is inevitably pumped into the environment which seriously contaminates water supplies and foodstuffs. So it is crucial to develop a single fluorescent probe for H2 S detection with high sensitivity and selectivity. Herein, a colorimetric and turn-on near infrared (NIR) fluorescent probe NRDNP based on benzophenoxazine was designed and synthesized by thiolysis of 2, 4-dinitrophenyl (DNP) ether as the specific reaction site strategy to achieve highly specific H2 S detection in living systems. The studies demonstrated that the probe NRDNP exhibited excellent sensing performance toward H2 S with an about 80-fold NIR fluorescence enhancement, a rapid response within 10 min, excellent sensitivity with a detection limit of 19 nM and good selectivity. Furthermore, the NRDNP is an optical sensor which visually changes in terms of the fluorescence colour/intensity upon sensing gaseous H2 S molecules. NRDNP has low cytotoxicity and has been successfully applied in the fluorescence imaging of H2 S in living cells, suggesting that it would be an effective tool for H2 S detection in living systems.